External Oblique Muscle Schwannoma: A Rare Anatomical Presentation. (3rd September 2019) - Paramythiotis, Daniel; Pagkou, Diamantoula; Moysidis, Moysis; Mantha, Niki; Cheva, Angeliki; Michalopoulos, Antonios
Abstract : Introduction . Schwannomas or neurilemmomas are rare, benign, and usually solitary lesions that arise from the nerve sheath. In the majority of cases, these tumors involve the extremities, head, neck, and trunk. Case Presentation . In the present study, a 52-year-old man presented to our surgical department for the evaluation of a symptomatic lump in his left lateral abdominal wall. CT and MRI confirmed the presence of a cystic mass located between the external and internal oblique muscles. Histopathology and immunohistochemistry confirmed it to be benign schwannoma. Discussion . Schwannomas have rarely been reported in the abdominal wall. To the best of our knowledge, this is the first case of schwannoma located in the left upper abdominal wall and the fifth case of abdominal wall schwannoma reported according to the reviewed medical literature. Conclusion . Benign schwannoma should be included in the differential diagnosis of cystic and symptomatic lesions of the abdominal wall. The treatment of choice is surgical excision, and recurrence is extremely rare.